2022
DOI: 10.1227/ons.0000000000000298
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Deep Brain Stimulation: High Accuracy and Streamlined Workflow

Abstract: BACKGROUND: A number of stereotactic platforms are available for performing deep brain stimulation (DBS) lead implantation. Robot-assisted stereotaxy has emerged more recently demonstrating comparable accuracy and shorter operating room times compared with conventional frame-based systems. OBJECTIVE: To compare the accuracy of our streamlined robotic DBS workflow with data in the literature from frame-based and frameless systems. METHODS: We retrospectively reviewed 126 consecutive DBS lead placement procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In addition, Giridharan et al (2022) used robotic stereotactic platform of ROSA for DBS surgery under general anesthesia, and used intraoperative fluoroscopic computed tomography for registration and postplacement verification. The robot used in our study can perform DBS surgery under local anesthesia, during which MER electrophysiological monitoring was used to assist in locating nuclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Giridharan et al (2022) used robotic stereotactic platform of ROSA for DBS surgery under general anesthesia, and used intraoperative fluoroscopic computed tomography for registration and postplacement verification. The robot used in our study can perform DBS surgery under local anesthesia, during which MER electrophysiological monitoring was used to assist in locating nuclear.…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of this tool can be attributed to the increased efficiency and precision associated with robotics. 7,17,18,24 Furthermore, advances in imaging technology and resolution have allowed for accurate direct targeting in asleep DBS. Here, we detail our technique for robotic stereotactic implantation of DBS electrodes in asleep patients in a less invasive manner.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies reported data on this method, with a target radial error of 0.91 ± 0.38 mm (n = 819 electrodes), operative time of 109.1 ± 50.5 minutes (n = 659), and total procedure time of 249.2 ± 72.3 minutes (n = 265). 5,[17][18][19][20][21][22][23] Four studies reported their use of a skull-mounted robot with optical array registration/navigation, with a target radial error of 1.12 ± 0.54 mm (n = 406 electrodes), operative time of 155.4 ± 36.5 minutes (n = 406), and total procedure time of 277.1 ± 38.2 minutes (n = 165). 7,[24][25][26] Three studies (including this study) reported the use of a floor-mounted robot with a frameless transient fiducial array, with a target radial error of 0.84 ± 0.54 mm (n = 631 electrodes), operative time of 182.4 ± 47.8 minutes (n = 315), and total procedure time of 311.9 ± 63.0 min (n = 315).…”
Section: Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations